Peran Literasi Digital Islami dalam Membentuk Karakter Pengguna Media Sosial - Eko Purwanto; Raihan Cakra Haryudin; Eri Febriansyah; Muhammad Ilyas; Ismail Mubarok; Dede Nur Zaman (International Forum of Researchers and Lecturers, 2026)
This research aims to analyze the role of Islamic digital literacy in shaping the character of social media users in the digital era. The approach used is qualitative descriptive with a library research method. Data was obtained from the Qur'an, hadiths, scientific journals, books, and relevant literature related to digital literacy, character education, and social media ethics from an Islamic perspective. Data analysis was carried out using content analysis techniques to identify the relationship between Islamic values and the behavior of social media users. The results of the study show that Islamic digital literacy plays an important role in shaping the character of social media users through the application of tabayyun principles, communication ethics, and digital responsibility. These values contribute to building honest, polite, critical, wise, and responsible character. Thus, Islamic digital literacy can be used as a strategy in creating positive, productive, and in accordance with Islamic values. This research provides a theoretical contribution to the development of Islamic-based digital literacy studies as well as practical contributions for educational institutions and society in building an ethical and characterful social media culture.